Cost-effectiveness of non-communicable disease prevention in Southeast Asia: a scoping review - Nguyen, Thi-Phuong-Lan; Rokhman, M. Rifqi; Stiensma, Imre; Hanifa, Rachmadianti Sukma; Ong, The Due; Postma, Maarten J.; van der Schans, Jurjen (Frontiers in Public Health, 2023)
Background: Cost-effectiveness analyses (CEAs) on prevention of non-communicable diseases (NCDs) are necessary to guide decision makers to allocate scarce healthcare resource, especially in Southeast Asia (SEA), where many low- and middle-income countries (LMICs) are in the process of scaling-up preventive interventions. This scoping review aims to summarize the cost-effectiveness evidence of primary, secondary, or tertiary prevention of type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVDs) as well as of major NCDs risk factors in SEA. Methods: A scoping review was done following the PRISMA checklist for Scoping Reviews. Systematic searches were performed on Cochrane Library, EconLit, PubMed, and Web of Science to identify CEAs which focused on primary, secondary, or tertiary prevention of T2DM, CVDs and major NCDs risk factors with the focus on primary health-care facilities and clinics and conducted in SEA LMICs. Risks of bias of included studies was assessed using the Consensus of Health Economic Criteria list. Results: This study included 42 CEAs. The interventions ranged from screening and targeting specific groups for T2DM and CVDs to smoking cessation programs, discouragement of smoking or unhealthy diet through taxation, or health education. Most CEAs were model-based and compared to a do-nothing scenario. In CEAs related to tobacco use prevention, the cost-effectiveness of tax increase was confirmed in all related CEAs. Unhealthy diet prevention, mass media campaigns, salt-reduction strategies, and tax increases on sugar-sweetened beverages were shown to be cost-effective in several settings. CVD prevention and treatment of hypertension were found to be the most cost-effective interventions. Regarding T2DM prevention, all assessed screening strategies were cost-effective or even cost-saving, and a few strategies to prevent T2DM complications were found to be cost-effective in certain settings. Conclusion: This review shows that the cost-effectiveness of preventive strategies in SEA against T2DM, CVDs, and their major NCDs risk factors are heterogenous in both methodology as well as outcome. This review combined with the WHO “best buys” could guide LMICs in SEA in possible interventions to be considered for implementation and upscaling. However, updated and country-specific information is needed to further assess the prioritization of the different healthcare interventions.